Comparative structural analysis of neuromuscular junctions in mice at different ages - Boaro, Sueli N. [UNESP]; Soares, Jair C. [UNESP]; König Jr., Bruno (Elsevier, 1998)
The authors studied the histochemical and ultrastructural modifications that occur in the neuromuscular junctions (NMJ) of fibularis longus muscles of mice with an age range of 3 to 21 months. Twenty-four male and female animals were killed at 3, 5, 14 and 21 months of age: 7 of them at 3 months, 4 of them at 5 month, 9 at 14 months and 4 at 21 months. The fibularis longus muscles were processed and their NMJ examined with the transmission electron microscope. The most relevant changes were associated with the degeneration and retraction of terminal axons, i.e., axons poor in synaptic vesicles with degenerated mitochondria, and exhibiting multivesicular bodies and vacuoles; exposed and widened junctional folds and cytoplasmic processes of Schwann cells located in the synaptic gutter. The presence of lysosomes or lipofuchsin in the juxtajunctional sarcoplasm was also noted. These observations suggest that the phenomena of retraction and budding occur in the NMJ with advancing age, with a predominance of events associated with degeneration, leading to profound changes in NMJ shape.
Keywords: Aging; Fibularis longus; Mouse; Neuromuscular junction; animal cell; animal tissue; cell ultrastructure; cell vacuole; histochemistry; lysosome; mitochondrion; muscle; nerve fiber; neuromuscular synapse; sarcoplasm; schwann cell; synapse vesicle; transmission electron microscopy; Acetylcholinesterase; Axons; Microscopy, Electron; Muscle Development; Muscle, Skeletal; Neuromuscular Junction; Vacuoles